Marketing Strategy of Coffee Shop Case Study: Rasa Kopi Bandung - Faiz, Muhammad; Putra, Bintang; Raihan, Muhammad; Riezki, Dian; Ariatin, Adrian (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In an era of rapid development, the coffee industry has also advanced significantly, leading to intense competition in the coffee market. This growth in trends has expanded the popularity of coffee, making it highly sought after. This phenomenon has made consumer preferences crucial for increasing purchasing interest, especially when employing "Word of Mouth Marketing" strategies that directly reach students at Telkom University through trusted word-of-mouth.This research employs a qualitative method, conducting direct interviews on-site. The study aims to analyze the marketing strategy of Rasa Kopi, a coffee shop located in Bandung. The findings indicate that the marketing strategy of Rasa Kopi successfully captures consumer attention.